2020
DOI: 10.1007/s11160-020-09598-9
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the effects of anthropogenic noise on fish reproduction

Abstract: Aquatic animals use and produce sound for critical life functions, including reproduction. Anthropogenic noise is recognized as a global source of environmental pollution and adequate conservation and management strategies are urgently needed. It becomes therefore critical to identify the reproductive traits that render a species vulnerable to acoustic disturbances, and the types of anthropogenic noise that are most likely to impact reproduction. Here, we provide predictions about noise impact on fish reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 169 publications
(225 reference statements)
2
56
0
Order By: Relevance
“…Continuous low frequency irregular noise has been claimed to increase stress levels and induce communication masking for fish. 36 Therefore, roadway noise that overlaps with the fish hearing and sound production band is a potential stressor. Low frequency noise may affect invertebrate larval development and behavior as well, 37,38 but its extent remains still unknown because of the lack of audition curves.…”
Section: Resultsmentioning
confidence: 99%
“…Continuous low frequency irregular noise has been claimed to increase stress levels and induce communication masking for fish. 36 Therefore, roadway noise that overlaps with the fish hearing and sound production band is a potential stressor. Low frequency noise may affect invertebrate larval development and behavior as well, 37,38 but its extent remains still unknown because of the lack of audition curves.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Holmes et al 60 found that some coastal fishes returned to pre-disruption behaviour after 20 min of motorboat noise exposure. However, behavioural habituation to continuous sounds of heavy ship traffic may hide physiological stress with a potential impact on survival and reproduction 60 63 , and general population maintenance 15 . To demonstrate the validity of the habituation hypothesis in our species, fish could be subject of experimental trials in controlled environments (aquaria or tanks), where individuals from high and low acoustically polluted areas are exposed to different levels of noise.…”
Section: Discussionmentioning
confidence: 99%
“…fishery in California revealed that fish elicit alarm responses [59] and reduced longline catches [67]. However, it should be noted that studies were conducted with caged fish, which may influence the observed behavior, as well as inhibit larger-scale movements such as flight or avoidance, although this depends on the size and design of the enclosure [18,68].…”
Section: Into a New Millennium With New Studies Drawing A More Complementioning
confidence: 99%
“…If so, the need for strong protection of spawning habitats may not be the most efficient advice to prevent potential negative impacts on fish stocks. Therefore, a large project investigating the effects of seismic on spawning behavior and spawning performance as well as avoidance was initiated in 2018; "Effects of sound on spawning behavior and reproductive success of cod" (Spawn-Seis) (https://prosjektbanken.forskningsradet.no/project/FORISS/280367?Kilde=FORISS &distribution=Ar&chart=bar&calcType=funding&Sprak=no&sortBy=score&sortOrder=de sc&resultCount=30&offset=0&Fritekst=SpawnSeis, accessed on 17 April 2021) From this project, there are indications that continuous noise may be more hazardous for fish reproduction than intermittent blasts [18]. However, loud impulsive noise has been shown to produce stress, which could affect the spawning output.…”
Section: Into the 2020s: Increasing Scientific Effortmentioning
confidence: 99%
See 1 more Smart Citation